Enlarging the EMU to the east: what effects on trade? - Ansgar Belke; Julia Spies (Institute for the Study of Labor (IZA), 2008)
The purpose of this paper is to assess the implications of the Economic and Monetary Union (EMU) accession of eight Central and Eastern European Countries (CEECs) on their share in EMU-12 imports. Overcoming biases related to endogeneity, omitted variables and sample selection, our results indicate that the common currency has boosted intra-EMU imports by 7%. Under the assumption that the same relationship between the explanatory variables and imports will hold for EMU-CEEC trade, we are able to predict the future impact of the Euro. Our findings suggest that except for the least integrated countries, Poland, Latvia and Lithuania, all CEECs can expect increases in the EMU-12 import share.
urn:nbn:de:101:1-20080825245
Keywords: F15; 330; Central and Eastern European countries; Euro area enlargement; gravity model; panel estimation; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; EU-Binnenhandel; Importnachfrage; Schätzung; EU-Staaten (Osteuropa); EU-Staaten